Progressive Worsening of Vitamin D Deficiency Is Associated With Adverse Clinical Outcomes in Surgical Intensive Care Unit Patients - Ahmed Bassam Rasheed; Zahraa Kamil Yousif; Ahmed Amer Abdulhussein; Marwah Mohammed Qasim; Ahmed Hashim Hammoodi (JOURNAL OF MEDICAL AND HEALTH SCIENCE, 2026)
General Background: Vitamin D deficiency is recognized as a major nutritional disorder associated with immune dysregulation, prolonged hospitalization, and increased mortality in critically ill populations. Specific Background: Surgical intensive care unit (SICU) patients are particularly vulnerable to hypovitaminosis D because of severe physiological stress, limited nutritional intake, and reduced sunlight exposure during hospitalization. Knowledge Gap: Despite increasing evidence linking vitamin D deficiency with adverse outcomes, limited prospective data are available regarding the severity distribution and prognostic significance of vitamin D deficiency among surgical ICU patients in Iraq. Aims: This study evaluated the prevalence of vitamin D deficiency and its association with clinical outcomes among SICU patients admitted to Ghazi AL Hariri Hospital for Surgical Specialties, Baghdad. Results: A prospective cohort study involving 240 SICU patients demonstrated that severe vitamin D deficiency was present in 53.5% of participants, while only 1.2% had normal vitamin D status. Severe deficiency was associated with prolonged SICU stay, increased treatment costs, and higher mortality rates. Patients with severe deficiency showed a mean SICU stay of 15.33 days, significantly longer than those with moderate or mild deficiency (P = 0.002). Multivariate analysis confirmed vitamin D deficiency as an independent predictor of adverse clinical outcomes. Novelty: The study introduces severity-based vitamin D classification in SICU patients and demonstrates its prognostic relevance in a critically ill surgical population. Implications: Early screening and correction of vitamin D deficiency may support risk stratification and clinical management strategies in surgical intensive care settings. Highlights: • Severe hypovitaminosis D predominated among critically ill surgical patients admitted to SICU.• Longer intensive care hospitalization was identified in patients with profound nutrient depletion.• Mortality and treatment expenditure increased across lower serum 25-hydroxyvitamin D categories. Keywords: Vitamin D Deficiency, Surgical Intensive Care Unit, Critical Illness, Mortality, Serum 25 Hydroxyvitamin D